The Correlation Between Phonological Knowledge and Pronunciation Ability - Mohammad Nurman (Journal of English Education and Teaching, 2021)
The purpose of this research is to know whether there is a significant correlation between phonological knowledge and pronunciation ability. The method used in this research is correlation design. Variable X is the students’ phonological knowledge and variable Y is students’ pronunciation ability. Population of this research is all of the fourth semester students. There are 80 students as population and the writer took 20 students as the sample.  The data are analyzed using Pearson Product Moment formula to know whether there is a correlation between phonological knowledge and pronunciation ability of the students. The result showed there is a correlation between phonological knowledge and pronunciation ability of the students. Based on the calculation that is obtained, rxy value from variable X and Y is 0,223. It is categorized as a low correlation. Whereas the result of the calculation use tcount formula. The tcount value is 1,002. It means that there is no a significant correlation between X and Y variable.